Games people play—toward an enactive view of cooperation in social neuroscience - Engemann, Denis A.; Bzdok, Danilo; Eickhoff, Simon B.; Vogeley, Kai; Schilbach, Leonhard (Frontiers in Human Neuroscience, 2012)
The field of social neuroscience has made considerable progress in unraveling the neural correlates of human cooperation by making use of brain imaging methods. Within this field, neuroeconomic research has drawn on paradigms from experimental economics, such as the Prisoner's Dilemma (PD) and the Trust Game. These paradigms capture the topic of conflict in cooperation, while focusing strongly on outcome-related decision processes. Cooperation, however, does not equate with that perspective, but relies on additional psychological processes and events, including shared intentions and mutually coordinated joint action. These additional facets of cooperation have been successfully addressed by research in developmental psychology, cognitive science, and social philosophy. Corresponding neuroimaging data, however, is still sparse. Therefore, in this paper, we present a juxtaposition of these mutually related but mostly independent trends in cooperation research. We propose that the neuroscientific study of cooperation could benefit from paradigms and concepts employed in developmental psychology and social philosophy. Bringing both to a neuroimaging environment might allow studying the neural correlates of cooperation by using formal models of decision-making as well as capturing the neural responses that underlie joint action scenarios, thus, promising to advance our understanding of the nature of human cooperation.